THE EFFECT OF IRRIGATION INTERVAL AND SOME ENVIRONMENTAL SUSTAINABILITY FACTORS ON GROWTH AND PRODUCTION OF COWPEA PLANTS - Rawaa G. Al-Hlfie,; Abeer D. Salman,; Wafaa A. Hussein, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted during the spring season of 2023-2024 and the fall season of 2024-2025 at the fields of the College of Agricultural Engineering Sciences, University of Baghdad, to investigate effects of irrigation intervals I1 ,I2 (3 and 6 days) , soil amendment with zeolite at three concentrations Z0 ,Z1,Z2 (0, 4, and 8 g. kg soil⁻¹), and foliar spraying with kaolin for three concentrations C0,C1,C2 (0, 0.5, and 1 g .L⁻¹). The results revealed that the treatment I1Z2C2 ​ significantly excelled in leaf area, chlorophyll concentrations, and yield for both seasons, achieving 31.0 dm², 21.5 mg per 100 g fresh weight, and 1984.7 g in the first season, and 34.08 dm², 23.6 mg per 100 g fresh weight, and 2526.3 g in the second season. In contrast, the treatment I2Z0C0 ​ significantly outperformed others in proline concentration, peroxidase enzyme activity, and antioxidant capacity (DPPH), recording 45.5 mg g⁻¹ dry weight, 1.09 absorption units g⁻¹ protein, and 73.3% in the first season, and 101.80 mg g⁻¹ dry weight, 4.400 absorption units g⁻¹ protein, and 92.0% in the second season.